Water‐mediated intermolecular interactions in 1, 2‐O‐cyclohexylidene‐myo‐inositol: a quantitative analysis. Issue 1 (6th December 2016) - Purushothaman, Gayathri; Juvale, Kapil; Kirubakaran, Sivapriya; Vemula, Praveen Kumar; Thiruvenkatam, Vijay
Abstract : In 1, 2‐ O ‐cyclohexylidene‐ myo ‐inositol, the hydroxy groups at positions 4 and 5 are in a trans configuration and a rationale is suggested for the difficulties in synthesizing 1, 2;4, 5‐di‐ O ‐cyclohexylidene‐ myo ‐inositol. The calculated structure was very similar to that of the experimental structure. Hirshfeld surface analysis with fingerprint plots demonstrated that the O—H…O interactions are the major intermolecular interactions. Lattice energy calculations suggested that dispersion is the major contributor to the crystal packing. Abstract : The syntheses of new myo ‐inositol derivatives have received much attention due to their important biological activities. 1, 2‐ O ‐Cyclohexylidene‐ myo ‐inositol is an important intermediate formed during the syntheses of certain myo ‐inositol derivatives. We report herein the crystal structure of 1, 2‐ O ‐cyclohexylidene‐ myo ‐inositol dihydrate, C12 H20 O6 ·2H2 O, which is an intermediate formed during the syntheses of myo ‐inositol phosphate derivatives, to demonstrate the participation of water molecules and hydroxy groups in the formation of several intermolecular O—H…O interactions, and to determine a low‐energy conformation. The title myo ‐inositol derivative crystallizes with two water molecules in the asymmetric unit in the space group C 2/ c, with Z = 8. The water molecules facilitate the formation of an extensive O—H…O hydrogen‐bonding network that assists in the formation of a dense crystal packing. Furthermore, geometrical optimization and frequency analysis was carried out using density functional theory (DFT) calculations with B3LYP hybrid functionals and 6‐31G(d), 6‐31G(d, p) and 6‐311G(d, p) basis sets. The theoretical and experimental structures were found to be very similar, with only slight deviations. The intermolecular interactions were quantitatively analysed using Hirshfeld surface analysis and 2D (two‐dimensional) fingerplot plots, and the total lattice energy was calculated.